Severe hemothorax due to traumatic fracture of thoracic vertebra - Keigo Ozono; Kiwa Son; Kenta Momii; Yoshihiro Morifuji; Naoki Ikenaga; Masafumi Nakamura (Surgical Case Reports, 2024)
Abstract Background Hemothorax occurs in approx. 0.4% of all chest injury patients, but hemothorax due to a thoracic vertebral fracture is rare. Case presentation A 76-year-old Japanese man was transported to our hospital for right hemothorax due to a car accident. We performed emergency hemostasis surgery and tried to stop the bleeding by several methods, but it was difficult to control the bleeding because the bleeding point was an artery branch that runs in front of the vertebral body. Conclusion It is important to be aware that a fractured vertebra can damage the aorta's arterial branch and follow a severe course.